Training and development of learning devices in the digital era at Asy-Syadzili junior high school Pakis Malang - Lilik Sri Hariani; Endah Andayani (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
The teaching and learning process is the core of educational activities in schools. There is an interaction between educators and students in the teaching and learning process. Good learning is possible to produce good graduates as well. The service was carried out at Asy-Syadzili Junior High School, Sumberpasir, Pakis, Malang Regency, which involved 31 teachers. Based on the results of the training preparation of learning devices in the digital era at Asy-Syadzili Junior High School, we can conclude that 85.7% of teachers understand the learning tools in accordance with the applicable curriculum; 71.4% of teachers can prepare lesson plans in the digital era; 57.1% of teachers are able to make IT-based learning media, and 57.1% of teachers are able to implement the plans and media that have been made in learning.